IMPLEMENTATION OF MOTT-SN PROTOCOL IN HOME SECURITY SYSTEM USING MICROCONTROLLER NODEMCU - Kevin Suharto; Mohammad Fajar; Hasniati (KHARISMA Tech, 2021)
This study aims to apply the MQTT-SN communication protocol to a low-cost home security system based on the NodeMCU microcontroller. Data was collected through literature studies and experiments. The designed home security system consists of MQTT-SN client, MQTT-SN Gateway, and MQTT broker. Home security system application designed to run on Android Smartphone devices. Evaluation results of the system with a number of nodes from 2 to 10 nodes show that the MQTT-SN protocol QoS performance such as delay, packet loss, and throughput is good and acceptable. The average size of the delivery packet of MQTT-SN is smaller than that of the MQTT protocol. In addition, the designed home security system successfully sent notifications to the user's mobile device in response to the detection of movement around the sensor location points installed.